TINJAUAN PENGGUNAAN E-VOUCHER PADA SISTEM PEMBAYARAN PAY-LATER DALAM PERSPEKTIF FIKIH MUAMALAH KONTEMPORER - Salsabila, Nuraini; Dahliya, Silfi; Firdaus, Rivany Rida (Universitas Siliwangi, 2022)
Currently, the use of the marketplace as an online shopping site is not a new thing. Effortless and varied payment systems make people turn to online shopping applications to buy their daily needs. Not to mention that recently there was a pay later payment system with the advantage of using this system, one of which was being able to use discount vouchers or free shipping. Thus, this article was created to discuss the law on the use of e-vouchers in pay later payment systems in online shopping transactions based on Islamic law and principles in a review of muamalah fiqh, especially in contemporary muamalah fiqh. The research method used in this article is a qualitative research method by collecting and analyzing secondary data in the form of journals, articles, books, mass media related to the research. The results of the discussion show that in the perspective of Islamic law, the use of vouchers for payment later is considered not under Islamic law. This pay-later transaction uses an al-qardh contract (debt receivable) where the user will borrow the money first and pay it at the end of the month, although it is helpful due to additional fees or fines, it causes the implementation of paying later to become usury. Thus, the use of vouchers in pay-later payments is included in usury nasi'ah because of the benefits obtained in the transaction and there is an additional loan principal if late payments.